POLA ASUH MAKAN PADA RUMAH TANGGA YANG TAHAN DAN TIDAK TAHAN PANGAN SERTA KAITANNYA DENGAN STATUS GIZI ANAK BALITA DI KABUPATEN BANJARNEGARA - Drajat Martianto; Hadi Riyadi; Rizma Ariefiani (Jurnal Gizi dan Pangan, 2011)
This study aimed to analyze the impacts of feeding practices on underfive children’s nutritional status in different level of household food security. The study design was a cross-sectional study. Data on feeding practices were collected through personal interviews used questionnaire and nutritional status was calculated by using WHO-NCHS z-score. The average scores of feeding practices among samples were categorized as low (54.4%) and children of group very food-insecure had the lowest score of feeding practices. There was a significantly difference among the groups in the scores of sample’s feeding practices. The study showed that about 86 percent of children were categorized as normal (BB/TB indicator), but there were 11.6 percent categorized as wasting, while 32.0 percent and 54.3 percent categorized as underweight and stunting, respectively. Statistical analyses showed significant difference in term of nutritional status. There was a significant correlation between child’s nutritional status (BB/U, TB/U and BB/TB) and household food security. The study showed that child’s nutritional status (BB/TB) was influenced by energy’s adequacy level.